MPFL Reconstruction in Skeletally Immature Patients: Comparison Between Anatomic and Non-Anatomic Femoral Fixation—Systematic Review - Georgios Kalinterakis; Iakovos Vlastos; Elina Gianzina; Savvas Dimitriadis; Konstantinos Mastrantonakis; Efstathios Chronopoulos; Christos K. Yiannakopoulos (Children)
Background: MPFL reconstruction in children with open physis may be challenging, as a major concern during the surgery is to preserve the distal femoral physis. The purpose of this study was to compare the complication rate and the patient-reported outcomes in skeletally immature patients who underwent MPFL reconstruction using an anatomic (A) or non- anatomic (NA) surgical technique. Methods: For this systematic review, the authors adhered to the PRISMA guidelines. The literature search was conducted from inception to 31 May 2024. Three databases were used: Pubmed, Scopus and Cochrane library. We included skeletally immature patients who underwent MPFL reconstruction for chronic or recurrent patellar instability. The included studies should describe the surgical technique, report clinical outcomes and complications. Patients with closed physis, prior ipsilateral knee surgery, concomitant surgical procedures except for lateral retinacular release, multiligament knee injury, congenital or acute patellofemoral instability, hyperlaxity or less than 12 months follow up were excluded. Risk of bias was assessed using ROBINS-I, MINORS and MCMS scores. Results: Data from 304 procedures were collected, of which 208 were performed using an anatomic technique and 96 using a non-anatomic technique. Patient age at the time of surgery ranged from 8 to 17 years. The follow-up time ranged between 12 and 116.4 months. Postoperative Kujala (−0.73, p = 0.55) and Tegner (−0.70, p = 0.80) scores were better in the anatomic group compared to the non-anatomic one. Higher rates of recurrent instability (OR 0.91; 95%CI 0.44–1.86, p = 0.85), redislocation (OR 1.21; 95%CI 0.42–3.51, p = 0.8), subluxation (OR 0.73; 95%CI 0.29–1.83, p = 0.62), a positive apprehension test (OR 0.92; 95%CI 0.27–3.13, p = 0.89), stiffness (decreased ROM) (OR 1.63; 95%CI 0.33–1.72, p = 0.54) and reoperation (OR 1.16; 95%CI 0.35–3.80, p = 0.8) were reported in papers using the anatomic technique. Conclusions: The findings of this systematic review reveal that there is no significant difference between anatomic and non-anatomic MPFL reconstruction techniques in terms of patient-reported outcomes and complications. Thus, the choice of surgical technique might be left up to surgeon’s preference. Further high-quality, pediatric-oriented studies with long-term follow–up are needed to better guide clinical decision-making.